Peningkatan Hasil Belajar Matematika Siswa SMK dengan Menggunakan Media Belajar Macromedia Flash - Khayroiyah, Siti; Nasutiom, Haryati Ahda (IAIN PADANGSIDIMPUAN, 2020)
The purpose of this research is to analyze the incarse in the learning outcomes between students whose leraning uses macromedia flash media and the students whose leraning using power point media. This research was conducted using quantitative research through quasi-experimental methods. This study includes two variables, namely learning using macromedia flash and power point as independent variable and learning outcomes as the dependent variable. In this study, researcheres used all students in the one of private high school in the Medanas a study population follwed by sample selection using a random sampling methods. The result obtained are class of XII A-3 as an experimental class and class of XII A-4 as control class. In collecting data, researchers used anÂ instrument in the form of a studentsâ€™s mathematics learning achievment test which was given twice, namely before being given learning using macromedia flash (pre test) and after being given learning using macromedia flash and power point (post test). Furthermore, hypotesis testing is performed on the data that has been obtained using the t-test with the help of the SPSS program. Hypothesis testing resukt show that increase in mathematics learning outcomes of students whose learning uses macromedia flash media is higher than students whose learning uses power points. Therefore, it is recomended that learning to use macromedia flash media be used as an alternative learning media for teachers to improve student learning outcomes and the other ability of students.